LOCAL MATERIALS RAMMED EARTH IN SUSTAINABLE MANNER - Abioso, Wanita Subadra; Farras, Maulana Naufal (Universitas Komputer Indonesia, 2024)
Sustainable design indicates that one of the criterions to achieve sustainability, is working with natural resources, local material in particular. Majalengka Regency, West Java province in Indonesia that has local material terracotta (clay) wishes to build its Cultural Centre. This proposed design utilizes local material terracotta (clay) that is mixed into rammed earth due to availability of the materials. The phases of the process of utilization will be expressed according to the cradle-to-grave paradigm, well known as Life-Cycle-Assessment (LCA), a method of assessment to sustainable product. The method is action research based on design models, including the method of LCA and method of design, and many aspects of the design that would be concerning sustainable manner. The sequential phases from a to z will show how designing with local material, in this case rammed earth, according to the assessment tool, responsible for the process of extraction–forming–usage–benefit–waste disposal. This proposed design hopefully will increase the willingness of designers to adopt and apply design with local material which is rarely utilized. Hopefully, the results will be popularizing the usage of local material to achieve more sustainable design Keywords: LCA; sustainable; terracotta; rammed earth